2014
DOI: 10.1681/asn.2013060596
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Dose-Dependently Stimulates Human Renal Proximal Tubule Transport by the Nitric Oxide/Guanosine 3′,5′-Cyclic Monophosphate Pathway

Abstract: Stimulation of renal proximal tubule (PT) transport by angiotensin II (Ang II) is critical for regulation of BP. Notably, in rats, mice, and rabbits, the regulation of PT sodium transport by Ang II is biphasic: transport is stimulated by picomolar to nanomolar concentrations of Ang II but inhibited by nanomolar to micromolar concentrations of Ang II. However, little is known about the effects of Ang II on human PT transport. By functional analysis with isolated PTs obtained from nephrectomy surgery, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…The institutional review board of the University of Tokyo School of Medicine approved the study and written informed consent was obtained from all subjects as described. 42,44 Measurement of NBCe1 activity in isolated PT The luminally collapsed fresh PT (S2 segment), microdissected manually without collagenase treatment, was incubated with an acetoxymethyl ester form of a pH-sensitive fluorescence dye 2 0 ,7 0 -bis(carboxyethyl)-5(6)-carboxyfluorescein (BCECF/AM; Dojindo, Kumamoto, Japan) and cell pH was monitored with a photometry system (OSP-10; Olympus, Tokyo, Japan). Prewarmed (38 1C) Dulbecco's modified Eagle's medium supplemented with 1 mmol/l norepinephrine and equilibrated with 5%CO 2 /95% O 2 gas was used for the peritubular perfusate as described.…”
Section: Human Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The institutional review board of the University of Tokyo School of Medicine approved the study and written informed consent was obtained from all subjects as described. 42,44 Measurement of NBCe1 activity in isolated PT The luminally collapsed fresh PT (S2 segment), microdissected manually without collagenase treatment, was incubated with an acetoxymethyl ester form of a pH-sensitive fluorescence dye 2 0 ,7 0 -bis(carboxyethyl)-5(6)-carboxyfluorescein (BCECF/AM; Dojindo, Kumamoto, Japan) and cell pH was monitored with a photometry system (OSP-10; Olympus, Tokyo, Japan). Prewarmed (38 1C) Dulbecco's modified Eagle's medium supplemented with 1 mmol/l norepinephrine and equilibrated with 5%CO 2 /95% O 2 gas was used for the peritubular perfusate as described.…”
Section: Human Samplesmentioning
confidence: 99%
“…20,[45][46][47] Bath HCO 3 À reduction (from 25 to 12.5 mmol/l) was repeated two or three times during the control period, and only PTs that showed constant cell pH responses were used for the analysis as described. 44 The NBCe1 activity was determined before and 8 min after insulin addition to the bath perfusate. In some experiments, 100 nmol/l wortmannin (Wako, Tokyo, Japan) was added to the bath perfusate to confirm the role of PI3-K. To compare the results between LETO and OLETF rats or between humans without and with insulin resistance, the basal and insulin-stimulated NBCe1 activities were determined in two to four PTs from each kidney sample and the averaged data were used.…”
Section: Human Samplesmentioning
confidence: 99%
“…However, recently, Shirai and colleagues found that in human cells, ANG II, unlike what was observed in other species, induced the dose-dependent and strong stimulation of human proximal tubular transport via the activation of AT1-dependent nitric oxide/guanosine 3', 5'-cyclic monophosphate/ERK [106]. Currently, the molecular mechanisms underlying species-specific differences in proximal tubular responses to the NO/cGMP pathway remain unknown [107].…”
Section: Dose-dependent Biphasic Effects Of Ang II In the Proximal Tumentioning
confidence: 99%
“…45 Interestingly, human PTs studied in vitro only exhibit a stimulatory transport response to AngII. 46 …”
Section: Renin Angiotensin System Regulates Pt Nhe3 Distribution and mentioning
confidence: 99%